2001
DOI: 10.1136/jcp.54.7.533
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transcription factor AP-2 in colorectal adenomas and adenocarcinomas; comparison of immunohistochemistry and in situ hybridisation

Abstract: (J Clin Pathol 2001;54:533-538)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 33 publications
1
53
1
Order By: Relevance
“…Others did detect AP-2a by immunohistochemistry in some prostate cancer specimens (Lipponen et al, 2000). In primary colorectal (Ropponen et al, 2001) and ovarian cancers (Anttila et al, 2000), AP-2a was detected in the nucleus or the cytoplasm of tumour cells. However, the presence of the transcription factor in the cytoplasm precludes its function in transcription.…”
Section: Discussionmentioning
confidence: 97%
“…Others did detect AP-2a by immunohistochemistry in some prostate cancer specimens (Lipponen et al, 2000). In primary colorectal (Ropponen et al, 2001) and ovarian cancers (Anttila et al, 2000), AP-2a was detected in the nucleus or the cytoplasm of tumour cells. However, the presence of the transcription factor in the cytoplasm precludes its function in transcription.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies indicate that the activity of AP-2a results in cell cycle arrest and that its activity relates to tumor suppression, 1,7,57,58 while other studies suggest that overexpression of AP-2a is carcinogenic. 9,59-61 Several investigators examined the status of AP-2 proteins in human tumor tissues to uncover their role in oncogenesis and their prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…AP-2 is one of the critical factors of neural gene expression (Mitchell et al, 1991) and various neural genes contain AP-2 binding sites in their regulatory regions. Loss of AP-2a expression has been associated with progression of melanoma , prostate cancer (Ruiz et al, 2004) and colorectal cancer (Ropponen et al, 1999(Ropponen et al, , 2001). In addition, immunohistochemical studies of human melanoma, breast and colorectal cancer specimens have revealed that loss of AP-2a coincides with poor prognosis (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Transfection of AP-2a into hepatoblastoma and colon adenocarcinoma cell lines, which lack endogenous AP-2a expression, has resulted in negative cell cycle control and cell growth inhibition in vitro (Pellikainen et al, 2003). Immunohistochemical studies have shown that downregulated cytoplasmic AP-2a expression was consistently seen in high grade and advanced Duke's stage tumors (Ropponen et al, 2001). In addition, low cytoplasmic AP-2a expression was seen in high-grade carcinomas (Ropponen et al, 2001), corroborating previous reports in which low AP-2a expression was associated with higher tumor malignancy and poor survival (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation